2012
DOI: 10.1111/j.1600-0412.2012.01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Does regular exercise during pregnancy influence lumbopelvic pain? A randomized controlled trial

Abstract: Objective. To study lumbopelvic pain in women randomized to a regular exercise program during pregnancy in comparison to women receiving standard antenatal care. Design. A two‐armed, two‐center, randomized controlled trial. Setting. St Olavs Hospital, Trondheim University Hospital and Stavanger University Hospital. Population. A total of 855 pregnant women were randomized to intervention or control groups. Methods. The intervention was a 12 week exercise program, including aerobic and strengthening exercises, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(132 citation statements)
references
References 31 publications
1
114
3
2
Order By: Relevance
“…However we did not perform a detailed pain-history (Fast et al 1990;Stafne et al 2012;Robinson et al 2014) and we did not make any clinical assessment to evaluate the condition, which may underestimate the results. On the other hand, the sample was drawn from a population attending pre-natal courses in private centers, and therefore was not definitive in its ability to delineate prevalence of lumbo-pelvic pain in other populations.…”
Section: Discussionmentioning
confidence: 99%
“…However we did not perform a detailed pain-history (Fast et al 1990;Stafne et al 2012;Robinson et al 2014) and we did not make any clinical assessment to evaluate the condition, which may underestimate the results. On the other hand, the sample was drawn from a population attending pre-natal courses in private centers, and therefore was not definitive in its ability to delineate prevalence of lumbo-pelvic pain in other populations.…”
Section: Discussionmentioning
confidence: 99%
“…After assessing the complete articles, 16 were excluded because they did not report interventions that were supervised or guided by physical therapists (9-11, 24-28); because they associated the exercises to manual therapy (29,30); because they were unpublished (theses and dissertations) (31)(32)(33); for lack of data (34); or because they did not relate the outcomes or interventions of interest (8,35). Thus, eight studies (36)(37)(38)(39)(40)(41)(42)(43), published between the years of 2005 and 2014, were included in this systematic review (Tables 2, 3 Eight RCT (36 -43) were included; one about low back pain (36), two about pelvic pain (37,38) and five about low back and/or pelvic pain (39 -43) . The size of the sample of the studies included in the review varied from 34 to 855 participants, with a total of 1781 pregnant women.…”
Section: Identified Studiesmentioning
confidence: 99%
“…As to the methodological quality of the studies, assessed with the PEDro Scale, seven studies (36)(37)(38)(39)(41)(42)(43) were considered to have high quality, with scores varying from six to eight points. Only one study (40) had low methodological quality.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…Inactivity may be a predisposing factor to painful experiences (30) and a cross-sectional study (3) showed that there is an association of gestational low back pain with the longer time spent in the lying position, independent of the mattress characteristic. However, for pregnant women with low back pain, rest may be a strategy to relieve symptoms, since our study revealed that the majority (76.7%) found pain relief at bedtime, sit or relax, not related to lumbar incapacity.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study (30) was carried out with 855 pregnant women aimed to evaluate a 12-week exercise program during the second half of pregnancy on the prevalence of lumbopelvic pain and the number of medical licenses in the period; revealed that the program did not appear to influence the prevalence, but significantly reduced the proportion of women applying for sick leaves for this condition. Those results suggested that they can cope better with the disorder compared to women who received standard prenatal care.…”
Section: Discussionmentioning
confidence: 99%